Genome-based Classification of Paenibacillus Litoralis sp. nov., Isolated from Coastal Soil in Dokdo, Republic of Korea - Chi Young Hwang; Eun Hee Bae; In-Tae Cha; Myung-Ji Seo (Current Microbiology, 2026)

Polymer semiconductor-coated 3D bilayer cellulose nanofiber/polydimethylsiloxane aerogel for enhanced solar-driven interfacial water evaporation - Keerthnasre Dhandapani; Gayoung Ham; Hossein Fattahimoghaddam; In Ho Kim; Hyojung Cha; Xiaowu Tang; Da Wan Kim; Tae Kyu An; Yong Jin Jeong (Desalination, 2025)

Revealing the Prokaryotic Microbial Community Structures and their Ecological Potentials in Manjanggul Cave, a Lava Tube on Jeju Island - Minji Kim; So-Jeong Kim; In-Tae Cha; Soo-Je Park (Current Microbiology, 2025)

Arvimicrobium flavum gen. nov., sp. nov., A Novel Genus in the Family Phyllobacteriaceae Isolated From Forest Soil - Hyosun Lee; Dhiraj Kumar Chaudhary; Ki-Eun Lee; In-Tae Cha; Won-Jae Chi; Sunho Park; Taegun Seo; Dong-Uk Kim (Current Microbiology, 2025)

Genome-based classification of Halobellus rubicundus sp. nov., a novel extremely halophilic archaeon isolated from a Korean solar saltern - Chi Young Hwang; Eui-Sang Cho; In-Tae Cha; Ki-Eun Lee; Eun-Young Lee; Myung-Ji Seo (Extremophiles, 2024)

Unraveling interspecies cross-feeding during anaerobic lignin degradation for bioenergy applications - Minji Kim; In-Tae Cha; Meng Li; Soo-Je Park (Chemosphere, 2024)

Chryseobacterium gotjawalense sp. nov. Isolated from Soil in the Volcanic Forest Gotjawal, Jeju Island - Minji Kim; In-Tae Cha; Ki-Eun Lee; Soo-Je Park (Current Microbiology, 2024)

Genomic insights and comparative analysis of Flavobacterium bizetiae HJ-32-4 isolated from soil - Jisu Kim; In-Tae Cha; Ki-Eun Lee; Youn Kyoung Son; Jaewoong Yu; Donghyeok Seol (Antonie van Leeuwenhoek, 2023)

Effects of edible insect extracts on the antioxidant, physiochemical, and microbial properties of Tteokgalbi during refrigerated storage - Hae In Yong; Tae-Kyung Kim; Ji Yoon Cha; Jae Hoon Lee; Min-Cheol Kang; Samooel Jung; Yun-Sang Choi (Food Bioscience, 2023)

The Role of Flavobacterium enshiense R6S-5-6 in the Wetland Ecosystem Revealed by Whole-Genome Analysis - Ahhyeon Choi; In-Tae Cha; Ki-Eun Lee; Youn Kyoung Son; Jaewoong Yu; Donghyeok Seol (Current Microbiology, 2023)
The wetland is an important ecosystem for purifying pollutants and circulating nutrients. Numerous microorganisms contribute to maintaining this function. We obtained Flavobacterium enshiense R6S-5-6 which was isolated from Ungok (Ramsar) Wetland and conducted whole-genome sequencing to investigate what contribution R6S-5-6 could make to the wetland community. The complete genome sequence of R6S-5-6 has a size of 3,251,289 bp with 37.68% of GC content. Gene annotation revealed that R6S-5-6 has several pathways to break down pollutants, including denitrification, assimilatory sulfate reduction (ASR), and polyphosphate-accumulating process. Furthermore, R6S-5-6 has genes that can have a positive effect on plants living in wetlands, such as storing essential nutrients, promoting plant growth, and protecting plants against pathogens.

Peptides inhibiting angiotensin-I-converting enzyme: Isolation from flavourzyme hydrolysate of Protaetia brevitarsis larva protein and identification - Jae Hoon Lee; Tae-Kyung Kim; Hae In Yong; Ji Yoon Cha; Kyung-Mo Song; Hyo Geun Lee; Jun-Geon Je; Min-Cheol Kang; Yun-Sang Choi (Food Chemistry, 2023)

Description of Microbacterium neungamense sp. nov. isolated from a hot spring - Dariimaa Ganbat; Ga Eul Jeong; DoKyung Oh; Dong-Woo Lee; Yong-Jik Lee; Seong-Bo Kim; In-Tae Cha; Won-Jae Chi; Seul-Ki Park; Jung-Sook Lee; Sang-Jae Lee (Archives of Microbiology, 2023)

Characteristics and adaptability of Flavobacterium panici BSSL-CR3 in tidal flat revealed by comparative genomic and enzymatic analysis - Jina Kim; In-Tae Cha; Ki-Eun Lee; Youn Kyoung Son; Jaewoong Yu; Donghyeok Seol (Archives of Microbiology, 2023)

Sulfitobacter albidus sp. nov., isolated from marine sediment of Jeju Island - Minji Kim; In-Tae Cha; Ki-Eun Lee; Soo-Je Park (Archives of Microbiology, 2022)

Fictibacillus marinisediminis sp. nov., a nitrate-reducing bacterium isolated from marine sediment in Hupo Basin, Republic of Korea - Eui-Sang Cho; Chi Young Hwang; Dong-Hyun Jung; In-Tae Cha; Myung-Ji Seo (Archives of Microbiology, 2022)

Haloferax litoreum sp. nov., Haloferax marinisediminis sp. nov., and Haloferax marinum sp. nov., low salt-tolerant haloarchaea isolated from seawater and sediment - Eui-Sang Cho; In-Tae Cha; Seong Woon Roh; Myung-Ji Seo (Antonie van Leeuwenhoek, 2021)

Parasphingorhabdus halotolerans sp. nov. isolated from marine sediment in Jeju Island - So-Jeong Kim; Minji Kim; Ki-Eun Lee; In-Tae Cha; Soo-Je Park (Archives of Microbiology, 2021)

Hymenobacter guriensis sp. nov., and Hymenobacter duratus sp. nov., Radiation-Resistant Species Isolated from Soil in South Korea - Tuvshinzaya Damdintogtokh; In-Tae Cha; Myung Kyum Kim (Current Microbiology, 2021)

Salinimonas marina sp. nov. Isolated from Jeju Island Marine Sediment - Minji Kim; Ki-Eun Lee; In-Tae Cha; Eui Tae Kim; Soo-Je Park (Current Microbiology, 2021)

Flavobacterium inviolabile sp. nov. isolated from stream water - Ve Van Le; Haeseong Lee; Shalem Raj Padakandla; In-Tae Cha; Ki-Eun Lee; Jong-Chan Chae (Archives of Microbiology, 2021)

Draconibacterium halophilum sp. nov., A Halophilic Bacterium Isolated from Marine Sediment - Minji Kim; Ki-Eun Lee; In-Tae Cha; Soo-Je Park (Current Microbiology, 2021)

Hymenobacter busanensis sp. nov., radiation-resistant species isolated from soil in South Korea - Sang Eun Lee; Leonid N. Ten; Yuna Park; Soohyun Maeng; Jing Zhang; Min-Kyu Kim; In-Tae Cha; Ki-Eun Lee; Byoung-Hee Lee; Hee ‑ Young Jung; Myung Kyum Kim (Archives of Microbiology, 2021)

Flexivirga aerilata sp. nov., Isolated from an Automobile Air Conditioning System - Dhiraj Kumar Chaudhary; Hyosun Lee; Ram Hari Dahal; Dae Hyun Kim; In-Tae Cha; Ki-eun Lee; Dong-Uk Kim (Current Microbiology, 2021)

Nakamurella aerolata sp. Nov., Isolated from an Automobile Air Conditioning System - Dhiraj Kumar Chaudhary; Hyosun Lee; Ram Hari Dahal; Dae Young Kim; In-Tae Cha; Ki-eun Lee; Dong-Uk Kim (Current Microbiology, 2021)

Spirosoma aureum sp. nov., and Hymenobacter russus sp. nov., radiation-resistant bacteria in Cytophagales order isolated from soil - Soohyun Maeng; Yuna Park; Joo Hyun Han; Sang Eun Lee; Jing Zhang; Min-Kyu Kim; In-Tae Cha; Ki-eun Lee; Byoung-Hee Lee; Myung Kyum Kim (Antonie van Leeuwenhoek, 2020)

Rhodocytophaga rosea sp. nov. and Nibribacter ruber sp. nov., two radiation-resistant bacteria isolated from soil - Yuna Park; Soohyun Maeng; Joo Hyun Han; Sang Eun Lee; Jing Zhang; Min-Kyu Kim; In-Tae Cha; Ki-eun Lee; Byoung-Hee Lee; Myung Kyum Kim (Antonie van Leeuwenhoek, 2020)

Pontibacter pudoricolor sp. nov., and Pontibacter russatus sp. nov. radiation-resistant bacteria isolated from soil - Soohyun Maeng; Yuna Park; Sang Eun Lee; Joo Hyun Han; In-Tae Cha; Ki-eun Lee; Byoung-Hee Lee; Myung Kyum Kim (Antonie van Leeuwenhoek, 2020)

Paenibacillus lutimineralis sp. nov., Isolated From Bentonite - Eui-Sang Cho; In-Tae Cha; Dong-Ho Seo; Young-Do Nam; Seong Woon Roh; Jae-Hwan Kim; Myung-Ji Seo (Current Microbiology, 2019)

Expression and characterization of glutamate decarboxylase from Lactobacillus brevis HYE1 isolated from kimchi - Hee Seon Lim; Dong-Ho Seo; In-Tae Cha; Hyunjin Lee; Young-Do Nam; Myung-Ji Seo (World Journal of Microbiology and Biotechnology, 2018)

Erratum to: Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2015)

Unveiling abundance and distribution of planktonic B acteria and A rchaea in a polynya in A mundsen S ea, A ntarctica - Jong‐Geol Kim; Soo‐Je Park; Zhe‐Xue Quan; Man‐Young Jung; In‐Tae Cha; So‐Jeong Kim; Kyoung‐Ho Kim; Eun‐Jin Yang; Young‐Nam Kim; Sang‐Hoon Lee; Sung‐Keun Rhee (Environmental Microbiology, 2014)
Summary Polynyas, areas of open water surrounded by sea ice, are sites of intense primary production and ecological hotspots in the A ntarctic O cean. This study determined the spatial variation in communities of prokaryotes in a polynya in the A mundsen S ea using 454 pyrosequencing technology, and the results were compared with biotic and abiotic environmental factors. The bacterial abundance was correlated with that of phytoplankton, P haeocystis spp. and diatoms. A cluster analysis indicated that the bacterial communities in the surface waters of the polynya were distinct from those under the sea ice. Overall, two bacterial clades, P olaribacter (20–64%) and uncultivated O ceanospirillaceae (7–34%), dominated the surface water in the polynya while the P elagibacter clade was abundant at all depths (7–42%). The archaeal communities were not as diverse as the bacterial communities in the polynya, and marine group I was dominant (> 80%). Canonical correspondence analysis indicated that the oceanographic properties facilitated the development of distinct prokaryotic assemblages in the polynya. This analysis of the diversity and composition of the psychrophilic prokaryotes associated with high phytoplankton production provides new insights into the roles of prokaryotes in biogeochemical cycles in high‐latitude polynyas.

Halapricum salinum gen. nov., sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - Hye Seon Song; In-Tae Cha; Kyung June Yim; Hae-Won Lee; Dong-Wook Hyun; Sung-Jae Lee; Sung-Keun Rhee; Kil-Nam Kim; Daekyung Kim; Jong-Soon Choi; Myung-Ji Seo; Hak-Jong Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2014)

Halobellus rufus sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Myung-Ji Seo; Daekyung Kim; Jong-Soon Choi; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; et al. (Antonie van Leeuwenhoek, 2014)

Halorubrum halophilum sp. nov., an extremely halophilic archaeon isolated from a salt-fermented seafood - Kyung June Yim; In-Tae Cha; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Sung-Jae Lee; Young-Do Nam; Dong-Wook Hyun; Jin-Woo Bae; Sung-Keun Rhee; Myung-Ji Seo; Jong-Soon Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halococcus sediminicola sp. nov., an extremely halophilic archaeon isolated from a marine sediment - Kyung June Yim; In-Tae Cha; Tae Woong Whon; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Young-Do Nam; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; Jong-Soon Choi; Myung-Ji Seo; et al. (Antonie van Leeuwenhoek, 2014)

Metabolic versatility of toluene‐degrading, iron‐reducing bacteria in tidal flat sediment, characterized by stable isotope probing‐based metagenomic analysis - So‐Jeong Kim; Soo‐Je Park; In‐Tae Cha; Deullae Min; Jin‐Seog Kim; Won‐Hyung Chung; Jong‐Chan Chae; Che Ok Jeon; Sung‐Keun Rhee (Environmental Microbiology, 2014)
Summary DNA stable isotope probing and metagenomic sequencing were used to assess the metabolic potential of iron‐reducing bacteria involved in anaerobic aromatic hydrocarbon degradation in oil spill‐affected tidal flats. In a microcosm experiment, 13 C‐toluene was degraded with the simultaneous reduction of F e( III )‐ NTA , which was also verified by quasi‐stoichiometric 13 C‐CO 2 release. The metabolic potential of the dominant member affiliated with the genus Desulfuromonas in the heavy DNA fraction was inferred using assembled scaffolds (designated TF genome, 4.40 Mbp with 58.8 GC mol%), which were obtained by Illumina sequencing. The gene clusters with peripheral pathways for toluene and benzoate conversion possessed the features of strict and facultative anaerobes. In addition to the class II ‐type benzoyl‐ CoA reductase ( B am) of strict anaerobes, the class I ‐type ( B cr) of facultative anaerobes was encoded. Genes related to the utilization of various anaerobic electron acceptors, including iron, nitrate (to ammonia), sulfur and fumarate, were identified. Furthermore, genes encoding terminal oxidases ( caa 3 , cbb 3 and bd ) and a diverse array of genes for oxidative stress responses were detected in the TF genome. This metabolic versatility may be an adaptation to the fluctuating availability of electron acceptors and donors in tidal flats.

Desulfotomaculum tongense sp. nov., a moderately thermophilic sulfate-reducing bacterium isolated from a hydrothermal vent sediment collected from the Tofua Arc in the Tonga Trench - In-Tae Cha; Seong Woon Roh; So-Jeong Kim; Hee-Ji Hong; Hae-Won Lee; Wan-Taek Lim; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Methanomethylovorans uponensis sp. nov., a methylotrophic methanogen isolated from wetland sediment - In-Tae Cha; Ui-Gi Min; So-Jeong Kim; Kyung June Yim; Seong Woon Roh; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Natronomonas gomsonensis sp. nov., isolated from a solar saltern - Tae-Yoon Kim; So-Jeong Kim; Soo-Je Park; Jong-Geol Kim; In-Tae Cha; Man-Young Jung; Sang-A Lee; Seong Woon Roh; Kyung June Yim; Takashi Itoh; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Hoeflea halophila sp. nov., a novel bacterium isolated from marine sediment of the East Sea, Korea - Man-Young Jung; Kee-Sun Shin; Suyeon Kim; So-Jeong Kim; Soo-Je Park; Jong-Geol Kim; In-Tae Cha; Mi-Na Kim; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Synaptic connections of calbindin-immunoreactive cone bipolar cells in the inner plexiform layer of rabbit retina - Shin Ae Kim; Choong Ki Jung; Tae-Hoon Kang; Ji Hyun Jeon; Jiook Cha; In-Beom Kim; Myung-Hoon Chun (Cell and Tissue Research, 2010)

Molecular authentication of ginseng cultivars by comparison of internal transcribed spacer and 5.8S rDNA sequences - Ok Tae Kim; Kyong Hwan Bang; Dong Su In; Jei Wan Lee; Young Chang Kim; Yoo Soo Shin; Dong Yun Hyun; Sung Sik Lee; Seon Woo Cha; Nak Sul Seong (Plant Biotechnology Reports, 2007)

Optimization of direct somatic embryogenesis from mature zygotic embryos ofPanax ginseng C. A. Meyer - Ok Tae Kim; Tae Soo Kim; Dong Soo In; Kyong Hwan Bang; Young Chang Kim; Yong Eui Choi; Seon Woo Cha; Nak Sul Seong (Journal of Plant Biology, 2006)